EFEKTIVITAS KAMPANYE SOCIAL MARKETING YUK NABUNG SAHAM DAN THEORY OF REASONED ACTION UNTUK MEMPREDIKSI NIAT BERINVESTASI SAHAM - Pipin Nur Azizi; Sanaji Sanaji (Jurnal Manajemen dan Pemasaran Jasa, 2018)
Indonesian Stock Exchange has launched a social marketing campaign program in 2015 to increase the number of new investors amid the low level of capital market utilization by society. This study aims to analyze and discuss the influence of social marketing campaigns to stock invest intention with attitude and the subjective norm in the TRA model as mediation variables. The type of this research is conclusive with a quantitative approach. The population is the student of Economics Faculty, State University of Surabaya. The questionnaire is distributed to 110 respondents and data was analyzed using a Structural Equation Model (SEM). The result shows that social marketing campaign has a significant positive effect on attitude and subjective norm, while attitude and subjective norm has a significant positive effect to stock investment intention, but social marketing campaign has no significant effect on investment intention. There is still inconsistency between this research result and previous research, the next research should analyze others variables that might affect stock invest intention.